1996
DOI: 10.1590/s0102-311x1996000100017
|View full text |Cite
|
Sign up to set email alerts
|

Uma experiência educacional de incentivo ao aleitamento materno e estimulação do bebê, para mães de nível sócio-econômico baixo: estudo preliminar

Abstract: This study included a preliminary analysis of the effectiveness of an educational program on breast-feeding and infant stimulation techniques. The program, developed by Garcia-Montrone (1992), was applied to a group of mothers (experimental group) of low socio-economic status. The program was evaluated by direct observation of mother-infant interaction and interviews with the mothers up to six months after childbirth. Results were compared with a control group of women matched for age, educational level, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
4

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 8 publications
0
3
0
4
Order By: Relevance
“…We excluded 79 studies from the review. The main reason for exclusion was because studies were not randomised trials, or it was not clear that allocation to groups had been carried out randomly; we excluded 18 studies identified by the search for this reason (Caulfield 1998; Davies-Adetugbo 1996; Ebbeling 2007; Garcia-Montrone 1996; Hall 2007; Jang 2008; Kistin 1994; McInnes 2000; Moreno-Manzanares 1997; Neyzi 1991; Nor 2009; Pascali-Bonaro 2004; Perez-Escamilla 1992; Segura-Millan 1994; Sisk 2006; Susin 2008; Thussanasupap 2006; Valdes 2000). A further two papers were reviews rather than reports of a randomised controlled trials (Guise 2003; Lewin 2005).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We excluded 79 studies from the review. The main reason for exclusion was because studies were not randomised trials, or it was not clear that allocation to groups had been carried out randomly; we excluded 18 studies identified by the search for this reason (Caulfield 1998; Davies-Adetugbo 1996; Ebbeling 2007; Garcia-Montrone 1996; Hall 2007; Jang 2008; Kistin 1994; McInnes 2000; Moreno-Manzanares 1997; Neyzi 1991; Nor 2009; Pascali-Bonaro 2004; Perez-Escamilla 1992; Segura-Millan 1994; Sisk 2006; Susin 2008; Thussanasupap 2006; Valdes 2000). A further two papers were reviews rather than reports of a randomised controlled trials (Guise 2003; Lewin 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Although outcomes included breastfeeding the main focus was on “maternal competence” and infant outcomes. 44% post-randomisation exclusions Garcia-Montrone 1996 Educational intervention. Controls were matched, but not randomised Gijsbers 2006 This study focused on families with a history of asthma. Guise 2003 Paper is a review. Haider 1996 Infants with diarrhoea.…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…Couri et al (2001) observaram em unidades básicas de saúde da cidade de São Paulo que, embora as mães tivessem bom conhecimento sobre a importância do aleitamento materno, determinadas situações práticas que freqüentemente promovem o desmame não tiveram índices satisfatórios, destacando que apenas o conhecimento não é suficiente para aumentar o período de aleitamento. O suporte dos serviços de saúde para a preparação das mães na superação de dificuldades circunstanciais que ocorrem durante a lactação é fundamental para o estabelecimento da mesma (Garcia-Montrone & Rose, 1996). Nesse sentido, as ações do Projeto Favela oferecem apoio constante às mães por meio das visitas domiciliares, sobretudo durante o primeiro mês de lactação, período mais critíco para o seu estabelecimento.…”
Section: Discussionunclassified
“…income and occupation) [13], parity [12], newborn’s prematurity [14], lack of access to antenatal care [15], and other health problems of the mother or the infant [13]. However, most of the evidence is focused on breastfeeding and bottle- feeding, and little has been built upon mixed-feeding practice (both breastfeeding and bottle-feeding) and how it differentiates from the other two feeding practices [16-20]. The most recent feeding survey in the UK found that 14% of mothers intended to mix-feed their babies from birth, compared with 61% who intended to exclusively breastfeed and 17% who intended to exclusively bottle-feed [5], although caution should be exercised when interpreting these figures as intention was assessed retrospectively.…”
Section: Introductionmentioning
confidence: 99%